NUSAP1 Promotes Gastric Cancer Tumorigenesis and Progression by Stabilizing the YAP1 Protein - Guo, Hui; Zou, Jianping; Zhou, Ling; Zhong, Min; He, Yan; Huang, Shanshan; Chen, Jun; Li, Junhe; Xiong, Jianping; Fang, Ziling; Xiang, Xiaojun (Frontiers in Oncology, 2021)
The Yes-associated protein (YAP1) is a main effector of the canonical Hippo pathway, which contributed greatly to tumor initiation, progression and metastasis in multiple cancers, including gastric cancer (GC). Due to the limited knowledge of YAP1 upregulation in cancer, it is a great challenge of the therapeutic targets towards the Hippo-YAP1 pathway. Here, we identify NUSAP1 as a novel binding partner of YAP1. The upregulation of NUSAP1 was associated with unfavorable clinical outcomes of GC patients, and NUSAP1 depletion impaired its oncogenic properties in vitro and in a xenograft model. Mechanistically, we discovered that NUSAP1 functions as a positive regulator of YAP1 protein stability, thereby inducing the transcription of Hippo pathway downstream target genes, such as CTGF and CYR61. More interestingly, we found that the cancer-promoting effects of NUSAP1 on GC cell growth, migration and invasion were mainly mediated by YAP1. Furthermore, aberrant expression of NUSAP1 and YAP1 was highly correlated in GC cell lines and tissues. We herein clarify that the oncogenic NUSAP1-YAP1 axis in GC tumorigenesis and progression, and therefore provide novel therapeutic targets for GC treatment.